Effects of annealing and extrusion on the microstructure and tensile properties of ultrafine-grained Al fabricated by spark plasma sintering. (20th October 2021) - Cao, Lei; Xie, Yuehuang; Luo, Yifei; Liang, Jiamiao; Wang, Jun; Zhang, Deliang; Wang, Limin
ABSTRACT: Ultrafine-grained Al samples were fabricated by spark plasma sintering (SPS) of a mechanically milled nanocrystalline powder. The effects of annealing and extrusion on the microstructure and tensile properties of the as-SPSed samples were investigated. Annealing removed the nanopores and caused significant coarsening of Al grains in the interparticle boundary (IPB) regions, leading to the formation of a heterogeneous structure consisting of coarse grains, ultrafine grains and Al4 C3 /Al2 O3 nanoparticles. Hot extrusion also eliminated the nanopores and resulted in the formation of a heterogeneous structure containing enhanced volume fraction of ultrafine grains and finer nanoparticles. These microstructural changes rendered a much improved YS and UTS of 251 and 288 MPa, respectively, and excellent tensile ductility (elongation to fracture: 12.7%). The improvement in mechanical properties can be attributed to grain boundary and nanoparticle strengthening, strain delocalisation of the heterogeneous structure and improvement of the bonding strength of IPBs.